How patients' experiences of respiratory tract infections affect healthcare-seeking and antibiotic use: insights from a cross-sectional survey in rural Anhui, China. Issue 2 (3rd February 2018) - Diao, Mengjie; Shen, Xingrong; Cheng, Jing; Chai, Jing; Feng, Rui; Zhang, Panpan; Zhou, Rongyao; Lambert, Helen; Wang, Debin
Abstract : Objective: To investigate the occurrence of reported respiratory tract infection (RTI) symptoms and their effects on use of self and professional care among patients in the community. Design: A cross-sectional retrospective household survey. Setting: 12 administrative villages from rural Anhui, China. Participants: 2160 rural adult residents aged ≥18 years registered as rural residents and actually living in the sampled villages when this study was conducted. Method: The respondents were recruited using stratified-clustered randomised sampling. A structured questionnaire was deployed to solicit information about social demographics, symptoms of last RTI and healthcare-seeking following the RTI. Descriptive analyses were performed to investigate the reported symptoms, and multivariate logistic regression models were developed to identify relationships between number of concurrent symptoms and healthcare-seeking and antibiotics use. Results: A total of 1968 residents completed the survey, resulting in a response rate of 91.1%. The number of concurrent symptoms showed a clear increasing trend with seeking help from clinics and being prescribed antibiotics. Multivariate regression revealed statistically significant associations between the following: (a) visiting clinics and education (OR=0.790), sore throat (OR=1.355), cough (OR=1.492), shortness of breath (OR=1.707) and fever (OR=2.142); (b) buying medicine from shops without prescription and education (OR=1.230) and cough (OR=1.452); (c) getting antibiotics at clinics and sore throat (OR=2.05) and earache and/or tinnitus (OR=4.884); and (d) obtaining antibiotics at medicine shops and productive cough (OR=1.971). Conclusions: Reported RTI symptoms play an important role in shaping both patient- and doctor-led responses.